Heavy metals contamination and risk assessment in sediments of Laucala Bay, Suva, Fiji. (July 2020) - Pratap, Arsita; Mani, Francis S.; Prasad, Surendra
Abstract: Spatial distribution of metals (Cd, Cr, Cu, Fe, Ni, Pb and Zn) were studied in the surficial sediments from 20 sampling sites of Laucala Bay Suva, Fiji to assess the significance of wastewater effluent discharged from Kinoya Wastewater Treatment Plant (KWWTP) into Laucala Bay as a major source. The bioavailability of these metals was also assessed using the fractionation technique. The total concentrations of individual metals varied from 1.7–6.0 mg/kg Cd, 24.2–49.1 mg/kg Cr, 54–170 mg/kg Cu, 13, 733–68, 492 mg/kg Fe, 23.5–34.8 mg/kg Ni, 50–80 mg/kgPb and 15.5–157.0 mg/kg Zn. All the metals studied except Ni showed significant increase around the KWWTP effluent discharge sites indicating that prolong discharge of wastewater could be a major source of their accumulation in Laucala Bay. The multivariate statistical analysis confirmed that Cd, Cu and Pb could be attributed to similar sources like wastewater effluent. The study confirmed that the spatial distribution of the metals in Laucala Bay was affected by the hydrodynamic of Laucala Bay as pollutants were dispersed from the point sources. The Risk Assessment Code (RAC) assessed from the bioavailable fraction data confirmed that apart from Cd and Pb, the rest of the metals analysed had medium risk of toxicity. Owing to the persistent nature of metals and the results obtained from this study, there is a high probability of these metals to accumulate and increase in concentration in the future which could also lead to increase in their risk of toxicity to living beings. Highlights: Metals in sediments were moderately polluted and show high enrichment since the baseline study. Multivariate analyses showed that KWWTP was the major source for Cu, Cd and Pb. As per SQGs most sites studied show values between ERL and ERM and need constant monitoring. The RAC analyses showed that Cd and Pb pose no toxicity threat to environment. According to RAC, medium risk of toxicity of Cr, Cu, Ni, Fe and Zn was noted in some sites.